Optimum Design of Pump Intake using CFD for Improving Hydraulic Performance - Farouk Elzahry, Elzahry; Ghanem, Ashraf (Applications of Modelling and Simulation, 2020)
A new El-Tabiya pumping station in Alexandria Governorate is considered in this work. The station consists of six axial pumping units. The old station is replaced by a new one and the old sump is reused. Pump operation depends not only on the efficiency of the pumping units but also on the proper design of the intake sump. Intake sumps receive water flowing from the intake channel and must direct it smoothly to the pump suction opening. If suction sumps are improperly shaped or sized, air-entraining vortexes or submerged vortexes are developed. The flow conditions at an entry to a pump depending upon flow conditions in approach channel, the various site-specific geometrical and hydraulic constraints, the location of pump intake with respect to the walls, velocity changes and obstructions such as piers, screens, etc., and rotational tendencies inflow produced upstream of the pump bays. The time and cost involved in-sump model studies for the design of sump geometry can be reduced to a large extent through Computational Fluid Dynamics (CFD) studies as the flow parameters can be predicted at the pump inlet with the change in geometry without actual running of the pump with CFD. Hence the design of the sump can be optimized to keep the flow parameters below limiting values. This study attempts to model the flow characteristic in a pump sump, minimize the swirl angles, increase the flow at the pump inlet and keep the flow parameters below limiting values. The numerical study carried out in this paper aims at optimizing the overall fluid flow in a pump intake by the use of a commercially available CFD code. CFD study was carried out on initial sump geometry and initial CFD results were analyzed.